A Boundary Value Problem for Hermitian Monogenic Functions. (24th December 2007) - Blaya, Ricardo Abreu; Reyes, Juan Bory; Peña, Dixan Peña; Sommen, Frank
Abstract : We study the problem of finding a Hermitian monogenic function with a given jump on a given hypersurface inℝ m,   m = 2 n . Necessary and sufficient conditions for the solvability of this problem are obtained.